2004
DOI: 10.1007/s00330-004-2543-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of right ventricular function by 16-detector-row CT: comparison with magnetic resonance imaging

Abstract: The purpose of this study was to determine right ventricular (RV) function from 16-detector-row CT by using two different software tools in comparison with MRI. Nineteen patients underwent cardiac CT. (1) With semiautomated contour detection software end-diastolic and end-systolic RV volumes were determined from short-axis CT reformations (MPR) created at every 10% of the RR-interval. (2) End-systolic and end-diastolic axial images were transformed to 3D to determine the volumes by using a threshold-supported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
90
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 25 publications
0
90
5
Order By: Relevance
“…Although the current study provides no direct intra-patient comparison between CMR and CT, previous studies demonstrated adequate correlation of RV volumes and function measured with 64-slice CT and those with CMR [7]. However, the more limited temporal resolution of 16-slice CT resulted in a systemic over-estimation of RV end-systolic volume [8].As also addressed by Winters et al, CT is associated with radiation and iodine contrast material. The radiation dose of 14 mSv in the current study is substantial, especially for relatively young patients who are likely to receive additional examinations and treatments associated with radiation.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Although the current study provides no direct intra-patient comparison between CMR and CT, previous studies demonstrated adequate correlation of RV volumes and function measured with 64-slice CT and those with CMR [7]. However, the more limited temporal resolution of 16-slice CT resulted in a systemic over-estimation of RV end-systolic volume [8].As also addressed by Winters et al, CT is associated with radiation and iodine contrast material. The radiation dose of 14 mSv in the current study is substantial, especially for relatively young patients who are likely to receive additional examinations and treatments associated with radiation.…”
mentioning
confidence: 59%
“…Although the current study provides no direct intra-patient comparison between CMR and CT, previous studies demonstrated adequate correlation of RV volumes and function measured with 64-slice CT and those with CMR [7]. However, the more limited temporal resolution of 16-slice CT resulted in a systemic over-estimation of RV end-systolic volume [8].…”
mentioning
confidence: 71%
“…With reconstruction of multiple slices of the short axis of the ventricle at 10 instances evenly distributed across the cardiac cycle, left-and right-ventricular function can both be analyzed. Quantitative estimations of ventricular function by MSCT have demonstrated good accuracy, with calculated ejection fractions within 10% of those obtained by means of MRI, 21,22 which is considered the most accurate method. Moreover, MSCT also detects abnormalities in wall motion.…”
Section: Multiple-slice Spiral Computed Tomographymentioning
confidence: 82%
“…Cardiac CT also provides adequate visualization of right ventricular (RV) volume and function, with studies showing good correlation of RV functional parameters obtained by CCT with MRI, angiography and echocardiography. [25,26] An important caveat to CCT's ability to workup cardiac function is that prospective ECG gating is increasingly employed in order to reduce the amount of radiation exposure, and it is not possible to assess ejection fraction and wall motion with this technique. In addition, the temporal resolution of CCT is limited compared to MRI and may impair its ability to obtain images in patients with higher heart rates.…”
Section: Heart Failure (Impaired Systolic Function)mentioning
confidence: 99%